26. WEIGHT LOSS IN CHILDREN AFTER HOSPITALIZATION: PREVALENCE AND RISK FACTORS AT DEPARTMENT OF INTERNAL MEDICINE 3 IN CHILDREN'S HOSPITAL 2 (Vietnam Journal of Community Medicine, 2025)
Objective: The study aimed to investigate the prevalence of weight loss and associated risk factors in hospitalized children at Department of Internal Medicine 3, Children’s Hospital 2 in 2025.Subjects and methods: A cross-sectional descriptive study was conducted on 178 childrens aged 0 to under 16 years who were admitted to Department of Internal Medicine 3, Children’s Hospital 2, from March to May 2025.Results: The prevalence of weight loss on day 3 of hospitalization was 42.1%. Among these, 32.0% lost less than 2% of their body weight, 53.3% lost 2–